Self-paced sport events under temporal constraints: Visual search, quiet eye, expertise and constrained performance time in far aiming tasks - Lee, S. M.; Kim, S.; Park, S. H. (International Journal of Applied Sports Sciences, 2009)
The purpose of this study was to examine the change of visual search strategies according to expertise and constrained performance time on far aiming tasks. For this research, constrained performance time was classified into 0%, 25% and 50% constraint conditions, and the participants were divided by expertise into 5 experts (M=7.2 year experience) and 5 non-experts (M=3.2 year). To analyze visual search behavior, the vision-in-action (VIA) system was used for the simultaneous recording of visual search behavior, motions, and ocular behavior of the participants while 10m distance air pistol comprised of shooting tasks were being performed. The VIA system was comprised of an eye movement tracking system (NAC EMR-8), two external digital video cameras, and a time code generator. For the research analysis, two-way repeated ANOVA was used. The major results obtained from this study were the following: first, the ratio of fixation time of the experts was higher than that of the non-experts. Second, the highest visual fixation frequency was recorded under 0% constrained performance time, and the visual fixation frequency was decreased by constrained performance time. Third, the experts displayed the longer visual fixation duration on the target. On the other hand, the non-experts displayed more searching eye movement toward the target. As constrained performance time increased, the experts showed more effective visual search strategy. Finally, the quiet eye (QE) duration of the experts was significantly longer than the non-experts and both groups showed QE duration decreases along with the increase of constrained performance time.